Medical alarms and auditory masking: the role of amplitude envelope - Mattar, Maya; Elizondo Lopez, Andres; Schutz, Michael (n/a, 2024)
Auditory alarms are essential for updating healthcare workers about patients. However, standard medical alarms are susceptible to auditory masking, which occurs when one sound renders another inaudible. Masking leads healthcare workers to miss alarms, putting patients at risk. Here, we investigated whether the risk of masking is affected by an alarm’s change in energy over time, called amplitude envelope. Although the current standard of medical alarms relies on sounds with constant “flat” envelopes, past research shows perceptual advantages in incorporating sounds with decaying “percussive” envelopes. Using the Medical Alarm Audibility System Checker (MAASC)—a computer modelling software developed by Hasanain et al. (2017)—we identified a configuration of standard medical alarms where one target alarm could theoretically be masked by two masker alarms. We synthesized flat and percussive versions of the alarms for comparison. In a 3AFC experiment, we asked participants to identify which of three presentations of the maskers also contained the target. The target volume varied according to a three-down one-up adaptive staircase model so that the target volume eventually converged on the masking threshold at which the target was barely audible over the masker. We compared thresholds between combinations of target and masker envelopes. Alarms were most resistant to masking when target and masker envelopes were heterogeneous, especially when a percussive target was paired with flat maskers. We recommend implementing envelope heterogeneity into medical alarm design to minimize masking, which will make alarms safer and more effective.
Keywords: medical/auditory alarms; auditory masking; amplitude envelope